A Study on the spatial form of traditional villages in jiangnan region of china from the perspective of human thermal comfort: A case study of nanjing, jiangsu province - Yao Xiong; Yinhui He; Xinyu Xie; Tingting Zhai; Ningling Chu; Lili Shen; Yunfeng Yang (PLoS ONE, 2025)
Traditional Chinese villages embody the ecological wisdom of ancient people to “conform to nature and transform nature”. In the long-term process of natural evolution, the natural environment and human production and living space have been combined to develop a unique spatial pattern with climate adaptability, which has the ability to cope with and regulate natural climate. Under the context of China’s rural revitalization, a study into the microclimate and thermal comfort of traditional villages holds promise for fostering the development of ecologically sustainable and aesthetically pleasing rural communities. This study focuses on three representative traditional villages in Nanjing. By employing a combination of measured data and ENVI-met numerical simulation, the microclimate effects of distinct spatial domains in these villages are analyzed. Additionally, the thermal comfort PET values are calculated using the Rayman platform, thereby objectively examining the relationship between spatial configuration and microclimate factors in Jiangnan traditional villages. The findings reveal that the PET values range from 38.4 to 57°C in summer and from 0.1 to 27°C in winter, with winter thermal comfort generally surpassing that of summer. From various villages. the internal water system of Shishanxia Village is scattered and the space is dense, with good ventilation and balanced humidity. Therefore, its thermal comfort in winter and summer is optimal. The northern mountain of Huanglongxian Village can effectively block the northwest monsoon and form a wind barrier, which can achieve the effect of keeping warm and controlling temperature in winter. Therefore, Huanglongxian has better thermal comfort in winter. Huashu Village is surrounded by water systems, with dense internal buildings and large hard areas inside the village. Plants are scarce, which can easily cause local high temperatures due to the absorption and radiation of solar radiation by hard underlying surfaces and buildings. Therefore, the comfort in winter and summer is the worst. Finally, the spatial configuration and landscape elements that influence human thermal comfort are revealed and transformation strategies tailored to each space type are summarized, aiming to provide scientifically grounded and rational recommendations for climate-adaptive design in rural areas.